IFAT FISIKO-KIMIA GELATIN KULIT IKAN BELUT DAN LELE PADA KEADAAN SEGAR DAN KERING - Hafni Rahmawati; Yudi Pranoto (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
Fish skin was a raw material for gelatin extracted. Fish skin drying was effectto physico-chemical of gelatin. Fresh fish skin and dry fish skin was compare tostudied gelatin extracted. Swamp ell skin and catfish skin was compare too. Swampell skin doesn’t have scales, with much mucus and a few fat for catfish, it’s different from another fish skin that gelatin extracted usually The first stage of the research was raw material preparation (fresh and dryfish skin) soaked in aquadest for 4 hours. Fish skin extracted using 0,05 M aceticacid for 10 hours, washed in water and then extracted using aquadest at 80oC for 2 hours to get gelatin liquid, the liquid was filtrated. Filtrat was dried in cabinet dryer at 55oC for 48 hours to get gelatin layers, and then blended to get gelatin granule.The results were showing viscosity of gelatin from dry fish skin as same asfrom fresh fish skin, gel strength and melting point of gelatin from dry fish skin washigher than from fresh fish skin. Influence of fish skin drying was increase turbidity and color of gelatin. The best gelatin was ekstracted from dry skin swamp ell withviscosity 6,65 cps, gel strength 206,30 Bloom, melting point 22,33oC. Gelatin fromfresh skin swamp ell was the best turbidity 1,65 ntu and color (L = 41,87, a = 8,90, b= 27,27).